KONSEP ANIMASI DALAM NOMINA BAHASA JAWA: SEBUAH KAJIAN TIPOLOGI ANIMASI AWAL - Khristianto Khristianto; Ambar Pujiyatno; Condro Nur Alim (Universitas Muhammadiyah Surakarta, 2021)
This study discussed the animacy concept in Javanese. This is to show how the animacy concept is reflected on pronouns and parts of the body, and behavioral verbs (agentive) between human, animal, and thing. This is a descriptive qualitative study employing the data from Javanese compared to English and Indonesia to clarify the animacy concept. The theoretical perspective used to analyze is the animacy concept from Comrie (1989). The analysis reveals that Javanese has no pronoun for non-human (animal and things), as the case in Indonesian. Meanwhile, English has it and there are pronouns for third person non-human, singular and plural. However it does not distinguish between animals and things. Thus, Javanese and Indonesia apply animacy hierarchy in their pronoun system. Another hierarchy is seen in the words to refer to body parts. It is only Javanese showing distinct characteristics; it uses high variants to refer to the human body. The same case is also found in the verbs (action) done by the human agent. Meanwhile two other languages do not apply this animacy hierarchy. Thus, the animacy hierarchy has a strongest influence on Javanese grammatical system, compared to the other two.